ЧИСЛЕННОЕ МОДЕЛИРОВАНИЕ ПОВЕРХНОСТНОГО ЭФФЕКТА В ФЕРРОМАГНЕТИКЕ ПРИ СИНУСОИДАЛЬНОМ МАГНИТНОМ ПОТОКЕ - Петухов, И.С. (Інститут електродинаміки НАН України, Київ, 2013)
A mathematical model for the skin effect in ferromagnetic medium based both on finite element method and time harmonics method was developed. A solution under condition of sinusoidal magnetic flux was given, and a comparison of the solution to the same, obtained upon excitation of the magnetic field by sinusoidal current, was performed. It is shown that even in the case of a sinusoidal magnetic flux the magnetic flux density on the surface and inside of the ferromagnetic is non-sinusoidal, and eddy current losses have higher values. References 9, figures 6.